Bilayer Tablets: Atorvastatin Calcium Nanoparticles and Clopidogrel Bisulfate Sustained Release Formulation - Subramanian, Dr. S. (Asian Journal of Pharmaceutics (AJP), 2017)
Background: Bilayer tablets are hopeful to deliver the different drugs in various release patterns to achieve the desired effect on patients with improved patient compliance. Atorvastatin is poor water soluble drug, and nanoformulation was adopted for enhancement of bioavailability whereas clopidogrel was tried with sustained release (SR) to achieve continuous antiplatelet action. Aim: The aim of the present study was to formulate and evaluate the bilayered tablets containing clopidogrel bisulfate in the SR portion and atorvastatin calcium nanoparticles in conventional release portion. Materials and Methods: To produce a single tablet containing two different classes of drugs and to enhance the bioavailability of atorvastatin calcium nanotechnology was employed using 2% surfactant of sodium lauryl sulfate to the ratio of drug atorvastatin and then subject to high-pressure homogenization and sonication, further, it was evaluated for particle size and zeta potential. The SR layer of clopidogrel bisulfate was prepared using polymers hydroxypropyl methyl cellulose and ethyl cellulose along with other excipients such as magnesium stearate, lactose, and talc by dry granulation technique. Then punched into bilayer tablet by two-run of the machine for each drug separately. Bilayer tablets were evaluated for their physical parameters such as weight variation, friability, hardness, and thickness and in vitro drug release study. Result and Discussion: Prepared atorvastatin nanoparticle was found to 677 nm in size with zeta potential of −17 mV and weight variation, friability, hardness and thickness that was within the limit. The in vitro drug release study showed that atorvastatin calcium nanoparticle of 99% at 15 min and clopidogrel bisulfate of 93.6% at 7 h and follows anomalous or non-Fickian type release (i.e.) Case-II type of release. In vivo study on rabbits proves an increase in relative bioavailability of atorvastatin calcium nanoparticles when compare to marketed product. Conclusion: The research outcomes are bilayer tablet of atorvastatin nanoparticles shown an increase in oral bioavailability on rabbits and in vitro study of clopidogrel bisulfate SR for better control over antiplatelet activity.